HIV infection and cardiovascular pathology - T. A. Shekhovtsova; D. V. Duplyakov (Кардиоваскулярная терапия и профилактика, 2023)
According to modern literature data, the role of human immunodeficiency virus (HIV) infection has been proven as an independent risk factor (RF) for atherosclerosis and cardiovascular diseases (CVDs), including coronary artery disease, heart failure, and sudden cardiac death. The role of antiretroviral therapy (ART) in the occurrence of CVD remains debatable. On the one hand, ART is a mandatory component in CVD prevention, since there are numerous confirmations of the association of high viral load and noncompensated immune status with an increased risk of CVD. On the other hand, the use of certain classes of ART agents is associated with the development of dyslipidemia, insulin resistance, and type 2 diabetes, which are risk factors for CVD. In this regard, the current HIV treatment protocols require an assessment of CVD risk factors to select the optimal ART regimen. It must be remembered that when using generally accepted algorithms and scales for assessing the risk of CVD, the real risk may remain underestimated in HIV-infected patients. This literature review presents a patient data management algorithm developed by the American Heart Association and describes statin therapy in patients with HIV infection.